The Complexities of Globalized Content Management. (April 2015) - Batova, Tatiana; Clark, Dave
This article provides a critical overview of the challenges that content management poses for technical communicators who work on multilingual projects. These issues include determining whether to translate or to localize, resolving the problems presented by the decontextualizing and repurposing of text, managing the complexities of the localization industry's work practices and tools, and handling the linguistic idiosyncrasies of particular languages. The authors draw on their experience with content management and the translation–localization industry in seeking to problematize increasingly standardized practices that deserve further investigation.